MUSICAL ABILITIES OF STUDENTS IN THE CONTEXT OF THE PROBLEM OF VOCAL AND CHORAL SKILLS FORMATION (Pedagogy of Higher and Secondary Education, 2010)
This article is reflected the describes components of musical abilities of pupils that affect the quality of forming vocal-chorus abilities, within components musical Unities. discusses such a notion as "musical ear", "feeling rhythm", musical memory", examines the shortcomings of the musical ear.
Keywords: musical abilities; performing abilities; musical ear; vocal ear; rhythm; musical memory; voice device; vocal-chorus abilities